The pharmacokinetics of therapeutic arsenic trioxide in acute promyelocytic leukemia patients. Issue 3 (23rd February 2022) - Ghiuzeli, Cristina M.; Stýblo, Miroslav; Saunders, Jesse; Calabro, Anthony; Budman, Daniel; Allen, Steven; Devoe, Craig; Dhingra, Radhika
Abstract: Arsenic trioxide (ATO) treats Acute Promyelocytic Leukemia (APL). ATO is converted from inorganic arsenic (iAs) to methylated (MAs) and dimethylated (DMAs) metabolites, which are excreted in the urine. Methylation of iAs is important in detoxification, as iAs exposure is deleterious to health. We examined ATO metabolism in 25 APL patients, measuring iAs, MAs, and DMAs. Plasma total iAs increased after ATO administration, followed by a rapid decline, reaching trough levels by 4–6 h. We identified two patterns of iAs metabolism between 6 and 24 h after infusion: in Group 1, iAs increased and were slowly converted to MAs and DMAs, whereas in Group 2, iAs was rapidly metabolized. These patterns were associated with smoking and different treatments: ATO with all-trans retinoic acid (ATRA) alone vs. ATO preceded by ATRA and chemotherapy. Our data suggest that smoking and prior chemotherapy exposure may be associated with ATO metabolism stimulation, thus lowering the effective blood ATO dose.